A organização da prática e o feedback pedagógico no ensino da natação - Monteiro, Gabriella Nelli (2018)
The aim of the present study was to identify how the practice and the pedagogical feedback ways are organized on the teaching-learning process of swimming. For that, it was necessary to validate the evaluation grid of the substantive contents and your organizations of practice and of the padagogical feedback for the swimming, to investigate how the swimming teaching works from the teachers point of view, to identify the different organizations and practice ways, substantive content and ways of pedagogical feedback in ministered classes and check the influence of the different organizations and ways of practice considering the different ways of pedagogical feedback. The study sample was composed by three experts of swimming in Brazil in the theoretical validation stage and six more swimming teachers registered in the regional physical education council (RPEC) in Cuiabá-MT, acting on the initiation of the learning aspect of swimming. For the theoretical validation of the grid was used the technique of content validity, to investigate how the swimming teaching works under the teachers point of view, were applied semi structured interviews in an individualized form trough the observation of two classes of each teacher, the grid allowed quantify by occurence’s frequency, the different organizations of practice of substantive content related to different ways of pedagogical feedback. For the analysis of the quantitative data the systematic observation was based on the absolute and relative frequency, the adhesion test and a multilayer perceptron model of neural networks and for the qualitative data was used the technique of content analysis. From the obtained results, a number of 28 items was validated by the content validity coefficient (CVC) considering values above 0.70, resulting from this process, the evaluation grid of substantive contents and their organizations of practice and of the pedagogical feedback for the swimming. The interviews generated 02 categories, 07 subcategories, 08 properties, obtaining a total of 214 mini-units that revealed that the teachers were insecure and showed a low knowledge about teaching methods, task organizations and technique and aplicattion of the feedback. The statistically significant differences between observed and expected frequencies showed the hegemony of the practice organization in block, in fractional form of practice, in the nature of task related to tecnique, in the feedback about the prescriptive goal, in the verbal form, in the individual supervision and in the performance on the teaching-learning of swimming against the other criterions in each category. It was concluded that the swimming teachers of the study organize their classes in block and teach the tecnique of fractional form. The most transmitted pedagogical feedbacks were the prescriptive, the verbal form, individually supervised and of performance criteria